2014
DOI: 10.1088/0965-0393/22/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic and austenitic phase transformations in Fe–C nanowires

Abstract: Using molecular-dynamics simulation, we study the austenitic and martensitic phase transformation in Fe–C nanowires with C contents up to 1.2 at%. The transformation temperatures decrease with C content. The martensite temperature decreases with wire diameter towards the bulk value. During the transformation, the bcc and fcc phases obey the Kurdjumov–Sachs orientation relationship. For ultrathin wires (diameter D ⩽ 2.8 nm), we observe wire buckling as well as shape-memory effects. Under axial tensile stress th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…While many available studies focus on the phase transformation behavior of ideal crystals of pure iron [11][12][13] or iron alloys [14][15][16][17], crystal defects may play a major role in the transformation behavior of iron. The influence of surfaces-in thin-film or nanowire geometries-was studied early on [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…While many available studies focus on the phase transformation behavior of ideal crystals of pure iron [11][12][13] or iron alloys [14][15][16][17], crystal defects may play a major role in the transformation behavior of iron. The influence of surfaces-in thin-film or nanowire geometries-was studied early on [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on cementite (Fe 3 C), and study the martensitic and austenitic transformations of an adjacent iron phase. Since previous studies demonstrated that the phase transformation behavior of Fe is only little influence by small alloying elements-such as C, Ni, or Cr [12][13][14][15]-the restriction to pure Fe appears justifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Since they deliver an atomistic view on the processes occurring in the sample during the transformation, they may be used to help understand the experimental results. [6][7][8] MD simulations studied the martensitic transformation in pure iron [9][10][11][12][13][14][15][16] and iron alloys [17][18][19][20][21] ; bulk samples as well as thin films 22 and nanowires 23,24 were studied. The transformation process follows in these cases well-known orientation relationships.…”
mentioning
confidence: 99%